FACTORS AFFECTING FARMERS' DECISIONS IN TRANSFER OF SIAM ORANGE LAND FUNCTIONS TO ARABICA COFFEE IN PARBULUAN DISTRICT, DAIRI REGENCY, NORTH SUMATRA PROVINCE - Juliana Juliana; Suryadi Suryadi; Irada Sinta (LPPM Universitas Malikussaleh - Indonesia, 2023)
The research was carried out in Parbuluan IV Village, Parbuluan District, Dairi Regency, North Sumatra Province from March 2022 to May 2022. The research method used was a survey method with a questionnaire as a tool. Sampling used the saturated sample method so that the number of samples obtained was 82 respondents. Data were analyzed using farm profit analysis and logistic regression analysis using SPSS software. The results showed that farming profits had a significant effect on farmers' decisions to change land functions and the variables of experience, age, education, land area, and fruit fly pests on Siamese oranges simultaneously had a significant effect on farmers' decisions in the conversion of Siamese orange land to Arabica coffee in Parbuluan District, Dairi Regency, North Sumatra Province. Variables of age, education.